Wind Speed Measurements in the Vicinity of a Tubular Mast: Influence of Data Selection Methods on Wind Speed Average Determination. Issue 2 (April 2014) - Farrugia, R. N.; Sant, T.
Wind measurements form an intrinsic part of the site selection process leading up to wind project development. Anemometers mounted on wind monitoring structures are expected to capture information on the free wind stream. However, the impacts of the structure and other hardware required to secure the sensors may have a marked influence on the data being compiled. This paper examines wind flow behaviour in the vicinity of an 80 metre tubular wind mast located at Ahrax Point on the Mediterranean Island of Malta. Mast and ancillary equipment effects are identified and quantified for two intermediate monitoring heights where dual and opposite anemometers were installed. A number of wind speed filtering methodologies are analysed in order to assess the methods' capabilities in reducing mast structure interference while enabling a conservative assessment of a site's wind potential.